2020
DOI: 10.1038/s41598-020-77061-7
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral oxytocin injection modulates vomeronasal sensory activity and reduces pup-directed aggression in male mice

Abstract: Behaviors are shaped by hormones, which may act either by changing brain circuits or by modifying sensory detection of relevant cues. Pup-directed behaviors have been previously shown to change via action of hormones at the brain level. Here, we investigated hormonal control of pup-induced activity in the vomeronasal organ, an olfactory sensory structure involved in the detection of non-volatile chemosignals. Vomeronasal activity decreases as males switch from a pup-aggressive state to a non-aggressive parenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 77 publications
1
21
0
Order By: Relevance
“…We previously showed that Gαi2 is necessary for the detection of small organic pheromones by apical VSNs, and genetic ablation of these neurons severely impairs pup-directed aggression in virgin males ( Trouillet et al, 2019 ). This is consistent with published studies that show that pup cues preferentially activate neurons located in the apical VNO and the anterior AOB in virgin males ( Tachikawa et al, 2013 ; Nakahara et al, 2020 ). Our results show higher c-Fos activation in the anterior AOB after pup-exposure ( Figures 1C,D ), indicating that pups are also preferentially detected by Gαi2+ VSNs in virgin females.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We previously showed that Gαi2 is necessary for the detection of small organic pheromones by apical VSNs, and genetic ablation of these neurons severely impairs pup-directed aggression in virgin males ( Trouillet et al, 2019 ). This is consistent with published studies that show that pup cues preferentially activate neurons located in the apical VNO and the anterior AOB in virgin males ( Tachikawa et al, 2013 ; Nakahara et al, 2020 ). Our results show higher c-Fos activation in the anterior AOB after pup-exposure ( Figures 1C,D ), indicating that pups are also preferentially detected by Gαi2+ VSNs in virgin females.…”
Section: Discussionsupporting
confidence: 93%
“…Not only centrally controlled neural changes, but also sensory organ sensitivity to olfactory stimuli have been suggested to have an influence. In particular, previous studies report a decline in VNO activity induced by pup cues in virgin males after cohabitation with a pregnant female ( Tachikawa et al, 2013 ; Nakahara et al, 2020 ), suggesting the existence of a silencing mechanism at the level of VSNs. We can thus speculate that a similar process may occur in females after parturition, either induced by hormonal changes intrinsic to gestation, or by repeated exposure to pups.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Oxytocin (OXT) is a nine amino acid neuropeptide that acts through the oxytocin receptor (OXTR) to generate physiological responses in adult mammals, such as facilitating milk let down for lactation, and labor and delivery. OXT also acts in the central nervous system to modulate social behavior by facilitating social learning and memory 1 , 2 , social recognition 3 5 , social reward 6 , 7 , pair-bond formation 8 , 9 , parental care 10 13 , sexual behavior 14 17 , and by reducing aggression 18 , 19 . Specifically, activation of OXT producing neurons in the paraventricular nucleus (PVN) of the hypothalamus and subsequent OXT release increases social behavior, while reduced activation of these neurons results in a decrease in social behavior 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Oxytocin (OXT) is a nine amino acid neuropeptide that acts through the oxytocin receptor (OXTR) to generate physiological responses in adult mammals, such as facilitating milk let down for lactation, and labor and delivery. OXT also acts in the central nervous system to modulate social behavior by facilitating social learning and memory 1,2 , social recognition [3][4][5] , social reward 6,7 , pair-bond formation 8,9 , parental care [10][11][12][13] , sexual behavior [14][15][16][17] , and by reducing aggression 18,19 . Specifically, activation of OXT producing neurons in the paraventricular nucleus (PVN) of the hypothalamus and subsequent OXT release increases social behavior, while reduced activation of these neurons results in a decrease in social behavior 20 .…”
Section: Introductionmentioning
confidence: 99%